The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/nu14010172
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective and Antioxidative Effects of the Traditional Thai Polyherbal Formula Phy-Blica-D against Ethanol-Induced Gastric Ulcers in Rats

Abstract: Phy-Blica-D is a traditional Thai polyherbal formula that has reduced oxidative stress in non-communicable diseases. However, evidence supporting the gastroprotective effects of Phy-Blica-D has not been previously reported. Therefore, this study aimed to evaluate the gastroprotective effects of Phy-Blica-D against gastric ulcers in rats and investigate the potential underlying mechanism. To estimate the possible mechanisms of action, we examined the levels of oxidative stress markers, such as reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…C. acaulis root methanol extract showed EC 50 of 208 µg/mL, while the essential oil of C. acanthifolia demonstrated EC 50 of 13.6 µg/mL according to DPPH assay. According some authors the anti-inflammatory and gastroprotective properties of this plant could be explained with the antioxidant activity [6,25,29]. Additionally, CH 2 Cl 2 extract of the C. acaulis roots demonstrated in vitro antioxidant activity by 2,2-diphenyl-1-picrylhydracyl assay and in vivo antioxidant activity was shown for C. elegans mode [15].…”
Section: Total Polyphenols and Antioxidant Activitymentioning
confidence: 98%
“…C. acaulis root methanol extract showed EC 50 of 208 µg/mL, while the essential oil of C. acanthifolia demonstrated EC 50 of 13.6 µg/mL according to DPPH assay. According some authors the anti-inflammatory and gastroprotective properties of this plant could be explained with the antioxidant activity [6,25,29]. Additionally, CH 2 Cl 2 extract of the C. acaulis roots demonstrated in vitro antioxidant activity by 2,2-diphenyl-1-picrylhydracyl assay and in vivo antioxidant activity was shown for C. elegans mode [15].…”
Section: Total Polyphenols and Antioxidant Activitymentioning
confidence: 98%
“…Thus the authors concluded that the concealment of oxidative stress and a rise in antioxidant activity could be responsible for the mechanism of the gastroprotective effect of Phy-Blica-D. As reported in the earlier findings, the phytoconstituents possessed free radical scavenging and gastroprotective effects, which could be responsible for the therapeutic benefit of the formulation. 25 ijlpr 2022; doi 10.22376/ijpbs/lpr.2022.12.6.P77-86…”
Section: Phy-blica-dmentioning
confidence: 99%
“…The pathophysiology of gastric ulcers is an imbalance between gastric mucosa-protecting and gastric mucosa-destroying due to acid secretions. Infectious diseases, smoking, stress, prolonged use of steroidal as well nonsteroidal antiinflammatory medicines, and excessive alcohol intake are also contributing factors that produce this imbalance [ 8 ]. Herbal medicines are alternative source of medicine that can cure a variety of gastroprotective mechanisms, such as the promotion of mucosal proliferation, suppression of acid, wound healing characteristics, production, and antioxidant capabilities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infectious diseases, smoking, stress, prolonged use of steroidal as well nonsteroidal antiinflammatory medicines, and excessive alcohol intake are also contributing factors that produce this imbalance [ 8 ]. Herbal medicines are alternative source of medicine that can cure a variety of gastroprotective mechanisms, such as the promotion of mucosal proliferation, suppression of acid, wound healing characteristics, production, and antioxidant capabilities [ 8 ]. The present study focused on demonstrating the chemical characterization through cold methanolic extraction and the ulcer healing properties of Lactuca sativa (LPL) leaf powder.…”
Section: Introductionmentioning
confidence: 99%